2016
DOI: 10.1590/1807-1929/agriambi.v20n12p1072-1077
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of guava rootstocks under salt stress

Abstract: A B S T R A C TThis study aimed to evaluate the tolerance of guava rootstocks under salt stress in the initial development stage. The experiment was conducted in a greenhouse in a randomized block design in a 5 x 3 factorial, consisting of five levels of irrigation water salinity (0.6, 1.2, 1.8, 2.4 and 3.0 dS m -1 ) and three guava rootstocks ('Crioula' , 'Paluma' and 'Ogawa'), with four replicates and four plants per replicate. Emergence, growth and phytomass accumulation were evaluated 30 days after sowing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Such a decrease in RDP can be considered a strategy that plants use to reduce the absorption of toxic ions, especially Na + and Cl -, and their consequent transport to the aerial part of the plant, hampering plant growth (Sá, Mesquita, Bertino, Silva, & Costa, 2013). A reduction in root dry phytomass accumulation due to salt stress has also been observed in other crops such as cashew (Lima et al, 2020b) and guava (Sá et al, 2016). Londrina, v. 42, n. 1, p. 137-154, jan./fev.…”
Section: Table 2 Summary Of the Analysis Of Variance For Stomatal Conmentioning
confidence: 75%
“…Such a decrease in RDP can be considered a strategy that plants use to reduce the absorption of toxic ions, especially Na + and Cl -, and their consequent transport to the aerial part of the plant, hampering plant growth (Sá, Mesquita, Bertino, Silva, & Costa, 2013). A reduction in root dry phytomass accumulation due to salt stress has also been observed in other crops such as cashew (Lima et al, 2020b) and guava (Sá et al, 2016). Londrina, v. 42, n. 1, p. 137-154, jan./fev.…”
Section: Table 2 Summary Of the Analysis Of Variance For Stomatal Conmentioning
confidence: 75%
“…is different and, as such, the translocation of Na and Cl between rootstocks, interstocks and shoots must take place differently. Sá et al (2016) conducted an experiment with the objective of evaluating the tolerance of three guava rootstocks ('Crioula' , 'Paluma' and 'Ogawa') under salt stress during the early stages of development where the treatments consisted of five levels of irrigation water salinity (0.6, 1.2, 1.8, 2.4 and 3.0 dS•m -1 ). The experiment showed that an increase in water salinity affected growth, biomass accumulation and number of leaves in the cultivars, having the most extreme effects at levels greater than 1.8 dS•m -1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out with salinity levels in plants of the 'Paluma' guava, Silva et al (2008) found symptoms of leaf toxicity as well as reduced growth and productivity at the lowest evaluated level (electrical conductivity of 2 dS•m -1 ). Sá et al (2016) reported that increased salinity restricted the emergence, growth and accumulation of biomass and the number of leaves in guava rootstocks, during the initial stages of development, with the most drastic effects at levels greater than 1.8 dS•m -1 . Silva et al (2017) reported that an increase in electrical conductivity (EC) from 0.3 dS•m -1 onwards negatively affected the morphophysiology of the guava rootstock 'Paluma' , especially during the earliest phase, also affecting the rate of growth of the stem diameter, shoot dry matter and root to shoot ratio (Souza et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…En el caso del guayabo, existen algunos reportes sobre la tolerancia a la salinidad. Sá et al (2016) probaron el efecto de cinco niveles de salinidad en el agua de riego (0.6, 1.2, 1.8, 2.4 y 3.0 dS m -1 ) por 30 d sobre la germinación de semillas de tres portainjertos de guayabo (Criolla, Paluma y Ogawa) y encontraron que el aumento en la concentración de sales restringe la germinación de las semillas, el crecimiento y la acumulación de biomasa y el mayor efecto ocurrió a niveles superiores a 1.8 dS m -1 . El número de hojas y biomasa seca total fueron las variables más afectadas por el estrés por sales.…”
Section: Crecimiento De Cultivares De Guayabo En Condiciones De Estréunclassified
“…Por último, la resistencia a salinidad se ha relacionado con la madurez del tejido, y aunque se reportó que la salinidad afectó la germinación de semillas de guayabo (Casierra-Posada, 2006) y el desarrollo temprano de las plántulas (Sá et al, 2016), las plantas evaluadas obtenidas a partir de estacas maduras presentaron mayor tolerancia a las CE evaluadas por un periodo de cuatro meses.…”
Section: Densidad Y Longitud De Estomasunclassified